2021
DOI: 10.22161/ijaers.88.51
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Relation to Adherence to Pharmacologic Treatment of Patients in Hemodialysis

Abstract: Objective: to analyze the relationship between health literacy and adherence to treatment of dialysis patients. Method: cross-sectional study with 424 end-stage renal disease patients on conventional HD in the West and Middle West of Santa Catarina. The SALPHA questionnaire was used to analyze health literacy and the Brief Medication Questionnaire was used for treatment adherence. Minimental was used to analyze cognition. Results: the mean age was 57.3±15.8 years, 53.3% men, 71.4% with low education level, 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The result showed that adherence to medication was related to all dimensions of the quality of life except the physical dimension. Health literacy is associated with medication adherence among patients with chronic kidney disease receiving hemodialysis (Barbosa et al, 2021;Fatima et al, 2022;Stømer et al, 2020). A previous study revealed that self-reported low medication adherence was associated with an increased risk for CKD progression (Cedillo-Couvert et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The result showed that adherence to medication was related to all dimensions of the quality of life except the physical dimension. Health literacy is associated with medication adherence among patients with chronic kidney disease receiving hemodialysis (Barbosa et al, 2021;Fatima et al, 2022;Stømer et al, 2020). A previous study revealed that self-reported low medication adherence was associated with an increased risk for CKD progression (Cedillo-Couvert et al, 2018).…”
Section: Discussionmentioning
confidence: 99%